Interference between resonant and Auger mechanisms for charge-exchange processes near surfaces - García, Evelina Andrea (2003)
In this work we solve the dynamics of the Newns-Anderson Hamiltonian supplemented with Auger termsand analyze the case of He1 scattered off an Al ~100! surface. The dynamical solution is compared with resultsof calculations based on much simpler approximations. We prove that resonant and Auger processes can betreated separately and independently in this case and that charge exchange between He and Al proceeds viaresonant and Auger exchange of electrons between the promoted molecular orbital of He and the conductionband states of Al.